Emotions, technology, design, and learning - Tettegah, Sharon Y.; Gartmeier, Martin (Amsterdam : Academic Press, 2015)
Emotions, Technology, Design, and Learning provides an update to the topic of emotional responses and how technology can alter what is being learned and how the content is learned. The design of that technology is inherently linked to those emotional responses. This text addresses emotional design and pedagogical agents, and the emotions they generate. Topics include design features such as emoticons, speech recognition, virtual avatars, robotics, and adaptive computer technologies, all as relating to the emotional responses from virtual learning.
Emotional Design in Digital Media for LearningThe Theoretical Foundation of Emotions and Learning; Toward an Integrated Cognitive-Affective Model of Multimedia Learning; Research Agenda for the Study of Emotional Design; Conclusion; Chapter 8: What Sunshine Is to Flowers: A Literature Review on the Use of Emoticons to Support Online Learning; Abstract; Introduction; Method; Emoticons and Electronically Mediated Communication; Emoticons and Group Differences; Emoticons and Social Contexts; Emoticons and Online Learning; Limitations and Gaps; Future Research; Instructional Recommendations.
CIP data; item not viewed.
Includes bibliographical references and index.
Keywords: Educational technology; Human-computer interaction; Human-computer interaction; Educational technology; Electronic books; Electronic books